1993
DOI: 10.7547/87507315-83-7-386
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of disinfectants against fungi isolated from skin and nail infections

Abstract: Commercial disinfectants classified as fungicides may not be effective against commonly encountered fungi within reasonable periods. Cell suspensions of clinical fungal isolates were exposed to use-dilutions of various disinfectants. Quaternary ammonium compounds, iodophors, and phenolics were not fungicidal against all test fungi within 60 min of exposure. Trichophyton mentagrophytes, Epidermophyton floccosum, and Aspergillus fumigatus were among the more resistant fungi. Disinfectants that possess low-level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…17 Experimentally contaminated dry surfaces (Petri dishes) were partly decontaminated by lengthy heating in an oven, but not by MW irradiation. We confirmed that 70% ethanol is highly effective for decontaminating dry surfaces [18][19][20][21] and also found that washing with soap and water before ethanol treatment has no added benefit.…”
Section: Naturally and Experimentally Contaminated Foodssupporting
confidence: 68%
See 1 more Smart Citation
“…17 Experimentally contaminated dry surfaces (Petri dishes) were partly decontaminated by lengthy heating in an oven, but not by MW irradiation. We confirmed that 70% ethanol is highly effective for decontaminating dry surfaces [18][19][20][21] and also found that washing with soap and water before ethanol treatment has no added benefit.…”
Section: Naturally and Experimentally Contaminated Foodssupporting
confidence: 68%
“…22 Our findings can probably be extrapolated to other potentially pathogenic yeasts and molds, because A fumigatus spores are highly resistant to physical and chemical disinfectants. [18][19][20][21]23 Few data are available on nonAspergillus molds. Fusarium species are sensitive to alcoholic solution 24 and to high water temperature, 25 and MW heating to the boiling point is a rapid and convenient method for eradicating Candida albicans from milk.…”
Section: Naturally and Experimentally Contaminated Foodsmentioning
confidence: 99%
“…The work of Terlecky & Axler [2] shows a considerable tolerance of T. mentagrophytes strains against various chemical disinfectants. Although, their study showed a high level of variability among T. mentagrophytes in resisting disinfectants, the isolates of T. mentagrophytes used in our study were only marginally different from each other.…”
Section: Discussionmentioning
confidence: 98%
“…These two modes adequacy of the washing procedure used in the present study. In other studies, a special washing formulation called Dey-Engley medium [2] has been used to neutralize disinfectants in suspension solutions. This medium is, however, rich in organic nitrogen, and the presence of amino acids and proteins is known to inhibit growth in certain Trichophyton species [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation